Effectiveness of neuro mobilisation on pain, range of motion, muscle endurance and disability in cervical radiculopathy: - a systematic review - Rafiq, Shazia; Zafar, Hamayun; Gillani, Syed Amir; Razzaq, Ayesha (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the effects of the neural mobilisation technique on mobility, pain and disability in cervical radiculopathy patients, and to assess the functional activity level Method: The systematic review was conducted from January 5 to July 5, 2022, and comprised search on Medline, PEDro, Cochrane Library and Embase databases for randomised controlled trials involving patients diagnosed with cervical radiculopathy that were published in the preceding 10 years in the English language. The search terms were divided into four classes by using the guideline for systematic reviews of trials of interventions in the Cochrane neck and back groups and related spinal disorders. Data was retrieved after the studies were subjected to quality assessment and risk of biasness. Result: Of the 1563 studies initially found, 8(0.51%) were reviewed. No matter the approach or dosage used, manual therapy was successful in treating cervical radiculopathy symptoms in all investigations. Conclusion: A multimodal strategy incorporating neural mobilisation appears to be the most successful short-term technique. Key Words: Cervical radiculopathy, Neural mobilisation, Muscle endurance.